TRANSFORMATION OF ISLAMIC RELIGIOUS EDUCATION IN THE ERA OF SOCIETY 5.0 - Muallimah Rodhiyana (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2023)
The development of the times makes the world today must prepare for the 5.0 revolution which makes us have to face fundamental changes including the way we live, work, and relate to one another. In the concept of era 5.0, the industry began to touch the virtual world, in the form of human, machine, and data connectivity. A transformation is a form of the change process that occurs gradually to achieve progress. Meanwhile, Islamic Education is an education system based on the main teachings of Islam and becomes a guide to achieving the expected educational goals. The transformation of Indonesian education in the Society 5.0 era began with the Merdeka Learning Independent Campus policy spearheaded by the Minister of Education, Culture, Research, and Technology. One of the priority activities of Merdeka Belajar is school digitization. To welcome the era of society 5.0, there must be a way out so that Islamic religious education can still be accepted during the times. Therefore, there are three steps that can be taken: 1). Disruptive Mindset, Mindset is how humans think which is determined by the settings we make before thinking and acting. 2). Self-Driving, Organizations that are agile and dynamic in adapting to navigate the ocean of disruption are organizations that have human resources (Human Resources) with good driver mentality (good drivers), not passengers (passengers). 3). Reshape or create, there is a genealogy of thought popular among Muslims which is still firmly held. The genealogy is "maintaining the old that is good and taking the new that is better." There is a process of modifying Islamic religious education in the era of Society 5.0.